Broadband Omnidirectional Diffuse Mirrors with Hierarchically Designed All-Dielectric Surfaces - Moon, Yoon Jong; Na, Jin Young; Park, Yong Hyun; Kim, Soo Bin; Lee, Sang Woon; Kim, Sun Kyung (ACS Photonics, 2018)
An electromagnetic wave with a single wave vector can be converted into multiple partial ones, with discrete or continuum wave vectors, by means of diffraction or scattering elements; this phenomenon is called optical diffusion. Optical diffusion is a crucial light-matter interaction problem, particularly for lighting applications that require uniform illumination. However, omnidirectional diffuse mirrors with minimal absorption loss have not been reported thus far. Here, we demonstrate the high-diffusivity, low-absorption reflecting surfaces, on which hexagonally arranged Al2O3 cones, with a pitch of 3 μm, are conformally covered with HfO2/Al2O3 multilayers. Spectrally resolved far-field measurements reveal that the hierarchically patterned surface diffuses reflected light uniformly over the entire range of azimuthal and polar angles at broadband wavelengths (λ = 400-800 nm), distinct to two-dimensional Al2O3 or Al patterned surfaces. Such omnidirectional optical diffusion is clearly identified by means of the momentum space representation; the hierarchical pattern allows all of the available diffraction modes to possess nearly equal amplitudes, which is strongly supported by near-to-far-field Fourier analysis. The degree of diffusivity is quantitatively evaluated with respect to different angular ranges (Δθ = 3°, 12°, and 24°) around a specular reflection angle. Under all of the considered metrics, the hierarchical pattern yields a relatively large diffusivity compared to the reference two-dimensional patterns. Measurements of reflectance spectra, together with full-vectorial electromagnetic simulations, suggest that the hierarchically patterned surface with a backside reflector serves as a high-reflectance diffuse mirror, contrasting with a patterned Al mirror that inevitably suffers from plasmonic absorption loss. These experimental and numerical findings studied herein will provide a fundamental platform for achieving omnidirectional optical diffusers.
Keywords: Far field; Far field measurement; Hierarchical patterns; Light-matter interactions; Lighting applications; Optical diffusers; Specular reflections; Two-dimensional patterns; diffraction gratings; far-field measurements; hierarchical patterns; near-to-far-field transform; Optical diffusers